Highly thermal conductive and electrically insulating polymer composites based on polydopamine-coated copper nanowire. (18th August 2018) - Yuan, Hao; Wang, Yang; Li, Ting; Ma, Piming; Zhang, Shengwen; Du, Mingliang; Chen, Mingqing; Dong, Weifu; Ming, Weihua
Abstract: Thermally conductive but electrically insulating polymer composites are highly desired for thermal management applications because of their ease of processing, light weight, and low cost. Copper nanowires (CuNWs), due to their inherent thermal conductivity and high aspect ratio, hold great potential in thermal management applications. However, CuNW-based polymer composites usually suffer from the deterioration of electrical insulating property. Therefore, it is critically required to reduce significantly the electrical conductivity of CuNW-based composites. In this study, highly thermally conductive but electrically insulating epoxy nanocomposites were prepared by incorporating polydopamine-coated CuNWs. At the volume fraction of 3.1% of CuNW, the thermal conductivity of the nanocomposites reached 2.87 W m -1  K -1, 14 times higher than pristine epoxy, while the electric resistivity remained to be greater than 10 14  Ω cm. These highly thermal conductive and electrically insulating nanocomposites are promising for applications in thermal management. Graphical abstract: Image 1